2006
DOI: 10.1111/j.1442-2042.2006.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma in dialysis patients: A single center experience

Abstract: Aim: Renal cell carcinoma (RCC) is a life-threatening complication of end-stage renal disease with an unclear pathogenesis. We evaluated RCC developing in patients undergoing dialysis. Methods: In 2624 patients undergoing hemodialysis or continuous ambulatory peritoneal dialysis at our hospital between July 1993 and March 2004, we performed annual screening for RCC using abdominal computed tomography and ultrasonography. Patients diagnosed with RCC underwent radical nephrectomy as well as clinical and patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 16 publications
8
54
1
3
Order By: Relevance
“…In United States, approximately 20% of those with ACDK will have RCC 5 . In Japan, Terasawa et al 4 , Satoh et al 29 and Kojima et al 11 reported 2.6% (41/ 1603), 0.61% (38/6201) and 1.68% (44/2624) of RCC in their patients on hemodialysis,respectively. Such an incidence of RCC appears significantly high, compared with that reported in the general Japanese population where RCC develops in 7.1 of 100000 men and 3.1 of 100000 women, and age-standardized incidence rates per 100 000 population for men and women were 4.9 and 1.8, respectively 30 .…”
Section: Incidence Of Rcc In Esrd Patientsmentioning
confidence: 99%
“…In United States, approximately 20% of those with ACDK will have RCC 5 . In Japan, Terasawa et al 4 , Satoh et al 29 and Kojima et al 11 reported 2.6% (41/ 1603), 0.61% (38/6201) and 1.68% (44/2624) of RCC in their patients on hemodialysis,respectively. Such an incidence of RCC appears significantly high, compared with that reported in the general Japanese population where RCC develops in 7.1 of 100000 men and 3.1 of 100000 women, and age-standardized incidence rates per 100 000 population for men and women were 4.9 and 1.8, respectively 30 .…”
Section: Incidence Of Rcc In Esrd Patientsmentioning
confidence: 99%
“…In East Asia, Cheung et al [34] reported that chronic dialysis patients showed a significantly higher incidence and mortality of kidney cancer than general population in Hong Kong while Chien et al [35] found that dialysis patients increased the risk of dying from kidney cancer compared to the general population in Taiwan. In Japan, Satoh et al [11] reported that 38 (0.6%) out of 6201 dialysis patients [12] reported that 44 patients (1.7%) were pathologically diagnosed with renal cell carcinoma in 2,624 dialysis patients between 1993 and 2004. These incidences of kidney cancer among dialysis patients appear higher than the incidence of general population (i.e., 7.1/100,000 for males and 3.1/100,000 [36]).…”
Section: Risk Factors Medical Conditionsmentioning
confidence: 99%
“…Satoh et al [11] conducted a retrospective cohort study of 6,201 chronic dialysis patients between 1990 and 2003, while Kojima et al [12] carried out a prospective cohort study of the 2,624 dialysis patients between 1993 and 2004 [12]. The final study is the summary of annual nation-wide questionnaire studies from 1982 to 2004 conducted by the Japanese Society for Dialysis Therapy [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations